Perancangan Sistem Pengunci Otomatis Berbasis Mikrokontroler Arduino Dengan Integrasi Keypad dan LCD - Hidayah, Delvina Salma; Ashidiqi, Pandu Dwi; ‘Izzatulhaq, Faaris; Mahendar, Irham Putra; Salsabila, Khalisa Putri (INTRO : Journal Informatika dan Teknik Elektro, 2024)
The development of an automatic locking system based on an Arduino microcontroller offers a modern solution to enhance security and access efficiency in various environments, such as homes, offices, or public facilities. This system integrates a keypad as an input device for access codes and an LCD as a display medium for user information. Using Arduino as the core controller, the system processes input from the keypad and provides visual feedback by displaying the lock status on the LCD. Additionally, the automatic locking feature enables the device to secure the door independently after a certain period, reducing the risk of user negligence. This study aims to design and implement a system that is simple, efficient, and user-friendly, focusing on security and practicality aspects. Testing results demonstrate that the system functions effectively, with high accuracy in code verification and resilience against unauthorized access attempts.